Alvin and the Chipmunks - Hill, Tim (Director); Karman, Janice; Bagdasarian, Ross; Vitti, Jon; McRobb, Will; Viscardi, Chris; Lee, Jason, 1970-; Cross, David, 1964-; Richardson, Cameron; Fox 2000 Pictures; Regency Enterprises; Bagdasarian Productions; et al. (United States : Fox 2000 Pictures, 2007)
A struggling songwriter named Dave Seville finds success when he comes across a trio of singing chipmunks: mischievous leader Alvin, brainy Simon, and chubby, impressionable Theodore.
Copyright Claimant: Twentieth Century Fox Film Corporation. Regency Entertainment (USA), Inc. Dune Entertainment III LLC. PREV: 2007, PAu 3-078-238. Pre-existing Material: feature screenplay entitled Alvin (PAu-3-078-238); based on the property entitled Alvin and the Chipmunks; music. Basis of Claim: All other cinematographic material. Date of Creation: 2007; Date of Publication: December 04, 2007; Registration Number / Date: PA0001590098 / 2007-12-06.
Summary from Internet movie database, viewed Feb. 13, 2008.
Not viewed.
Sources used: Copyright database; Variety Web site, review posted Dec. 13, 2007, viewed Feb. 13, 2008; Internet movie database, viewed Feb. 13, 2008; FirstSearch, OCLC 191914393, viewed Feb. 13, 2008.
Executive producers, Karen Rosenfelt, Arnon Milchan, Michele Imperato Stabile, Steve Waterman ; camera, Peter Lyons Collister ; editing, Peter Berger ; music, Christopher Lennertz.
Jason Lee, David Cross, Cameron Richardson, Jane Lynch.
Keywords: Chipmunks -- Drama; Lyricists -- Drama; Children's films; Animal films; Animated films; Feature films; Fiction films